Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 4740 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Lindernia crustacea (L.) F.Muell." ] } The dataset includes 4740 records from 140 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0007697-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences